The Analysis of Mastering of Concepts and Misconceptions in Elementary Teacher Education Students - Susanti, Maria Melani Ika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze the mastery of the concepts and misconceptions of heat material in students of the Elementary Teacher Education Study Program. This type of research is descriptive quantitative. The research subjects were 47 students. Collecting data in this study through online test evaluation with a google form. The results of this study were the mastery of the concept and misconceptions of heat material in the Elementary Teacher Education Study Program students from the 10 questions given, there were 5 questions that had a concept mastery percentage of more than 50%, while the other 5 questions students experienced misconceptions with a percentage of more than 50%. This misconception will have implications for the mastery of student concepts at the next stage and especially for students who become learning subjects when students become teachers.